The Wiley Blackwell Encyclopedia of Urban and Regional Studies 2019
DOI: 10.1002/9781118568446.eurs0472
|View full text |Cite
|
Sign up to set email alerts
|

Place

Abstract: Place refers to specific locations that have been made meaningful and useful by human beings. This entry articulates how location, locale, and sense of place are used to develop the concept of place and how disciplines such as geography, sociology, and anthropology understand and use the concept (including its distinction from space ). Particular attention is paid to how places develop meaning through deliberate and informal means and to how individuals' status and identity inform their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…(P11)Furthermore, a level of empowerment of SMBCs was also evident from P1, who indicated that a level of decorum was required to engage with online networks. This level of involvement extends beyond the role of the supporter, to empowered participants who are motivated to create a more usable and meaningful (Paulsen, 2010) digital space:You have to respect it [SMBC] if you want to be part of the family, you have to behave like you ’ re part of it, that ’ s the way I feel about it. We are part of the family all of us.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(P11)Furthermore, a level of empowerment of SMBCs was also evident from P1, who indicated that a level of decorum was required to engage with online networks. This level of involvement extends beyond the role of the supporter, to empowered participants who are motivated to create a more usable and meaningful (Paulsen, 2010) digital space:You have to respect it [SMBC] if you want to be part of the family, you have to behave like you ’ re part of it, that ’ s the way I feel about it. We are part of the family all of us.…”
Section: Resultsmentioning
confidence: 99%
“…By offering supporters the opportunity to interact and engage with each other by discussing aspects of the club and the locale around the ground, members unwittingly are involved in placemaking activities. Hence, the SMBCs observed in this study have become pivotal to creating “useful and meaningful” digital spaces, concerned with physical places, offering a modern-day perspective that harks back to Paulsen (2010).…”
Section: Theoretical Contributionsmentioning
confidence: 93%
See 1 more Smart Citation
“…At the same time, Givat-Amal’s new signage illustrates a prominent issue in the scholarship on place attachment, which is the (in-)ability of individuals to anticipate future interactions of the type they have enjoyed in the past. This might occur if a dramatic change occurs such that people can no longer imagine engaging in the interactions they valued; and upon displacement processes, when residents are forcibly evicted from their homes by redevelopment plans or disaster (Paulsen, 2019). In addition, the signage conveys that present uncertainties in Givat-Amal facing the threat of displacement are highly disruptive to people’s lives.…”
Section: Toponymic Extra-formality As “Place Attachment” In Givat-amalmentioning
confidence: 99%
“…In this article and within the broader concept of “place making,” we strive to highlight another, more specific concept, which is key for the following second part of the study, namely, “place attachment.” This describes “the emotional or affective bonds between people and places,” with close attention to neighborhood scale and the everyday, and to “processes of meaning-making that transform space into place ” (Paulsen, 2019: 1). It includes elements such as the extent to which residents are dependent on the place to sustain their needs; the centrality of the place in their self-identity through memories and life events; and their ability to anticipate their mundane interactive routine in the place in the near or far future (Paulsen, 2019). The last element is of special importance, as the historiography of the concept points to considerable attention assigned by scholars to situations of forced removals and displacement due to environmental disaster or economically beneficent redevelopment schemes (Anguelovski, 2013; Mah, 2012; Marris, 1961).…”
Section: Laying Out a Critical Urban-cum-legal Perspective: Introduct...mentioning
confidence: 99%